Composition and nutritive value of pejibaye (Bactris gasipaes) in animal feeds - Zumbado, Mario E. (1984)
Nutritive assesment of pejibaye (Bactris gasipaes) meals included proximal composition of the lipid and nitrogenous fractions. Caloric values obtained as true metabolizable energy (TME) indicate that the pejibaye has a higher content of energy than corn and that it is not necessary to separate the seeds from the fruits in animal feeds; the level of indispensable aminoacids is considerably low, especially methionine, which is lower than in corn; thin layer chromatography shows that most of the free fatty acids are present in a ratio of 2 : 1 in unsaturated to Saturated acids. The predominant fatty acids in whole pejibaye meal are oleic and palmitic acids with adequate levels of linoleic acid. Saturated fatty acids are predominant in the seed, with a very high content of lauric and myristic acids.